Penerapan Program Partnership with Parents Terhadap Kontinuitas Perawatan Anak dengan Stunting - Lydia Moji Lautan; Yustina Riki Nazarius; Fransiska Romina (Universitas Malahayati Lampung, 2026)
ABSTRACT Stunting is a growth disorder where a child's height falls below the age-standardized average due to prolonged malnutrition and recurrent infections. This condition demands special attention through continuous care that actively involves the family. This study aims to analyze the effect of the Partnership With Parents (PWP) program on the continuity of care for stunted children. This study used a quantitative approach with a quasi-experimental one-group pretest-posttest design was employed. The sample consisted of 35 mothers whose children were undergoing stunting treatment at UPT Puskesmas Saigon, Pontianak. Data were collected using a continuity of care questionnaire covering information, management, and relational dimensions. The Wilcoxon signed-rank test (α = 0.05) and effect size analysis were used. The PWP program significantly affected continuity of care across all dimensions (p 0.05). Effect sizes indicated very strong influences, with the highest in the management dimension (r = 0.965), followed by relational (r = 0.921) and information (r = 0.912) dimensions. The PWP program effectively improves continuity of care for stunted children by enhancing parents' ability to understand information, manage care, and build relationships with health workers. Keywords: Partnership with Parents, Continuity of Care, Stunting, Family-Centered Care. ABSTRAK Stunting merupakan kondisi tinggi badan anak yang berada di bawah rata-rata usianya akibat kekurangan gizi berkepanjangan dan infeksi berulang. Kondisi ini memerlukan perhatian khusus melalui perawatan berkelanjutan dengan keterlibatan aktif keluarga. Penelitian ini bertujuan menganalisis pengaruh program Partnership With Parents(PWP) terhadap kontinuitas perawatan anak stunting. Metode Penelitian menggunakan pendekatan kuantitatif dengan desain kuasi-eksperimen one-group pretest-posttest. Sampel berjumlah 35 ibu dengan anak stunting yang sedang menjalani perawatan di UPT Puskesmas Saigon, Pontianak. Pengumpulan data menggunakan kuesioner kontinuitas perawatan yang mencakup dimensi informasi, manajemen, dan relasional. Analisis menggunakan uji Wilcoxon (α = 0,05) dan effect size. Program PWP memberikan pengaruh signifikan terhadap kontinuitas perawatan pada seluruh dimensi (p 0,05). Nilai effect size menunjukkan kekuatan pengaruh sangat besar, dengan tertinggi pada dimensi manajemen (r = 0,965), diikuti dimensi relasional (r = 0,921) dan informasi (r = 0,912). Program PWP efektif meningkatkan kontinuitas perawatan anak stunting melalui peningkatan kemampuan orang tua dalam memahami informasi, mengelola perawatan, dan membangun hubungan dengan tenaga kesehatan. Kata Kunci: Partnership With Parents, Kontinuitas Perawatan, Stunting, Family-Centered Care.